Website-Based E-Learning Management System Case Study at SDN Cijantung 02 - Nugroho, Dimas Wahyu; Rosalina, Ria (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2022)
The development of information technology is increasingly sophisticated not only as a communication tool, but is used as a medium to support teaching and learning activities, many educational institutions including elementary schools have implemented information technology in the learning process through the web, one of which is known as e-learning. E-learning is education that uses an electronic system that supports the development of teaching and learning activities with internet media or other computer network media. With the existence of e-learning, the teaching and learning process becomes simple where students and teachers do not have to meet face to face. The method used is data collection methods, namely observation, interview and literature study. In this study, a waterfall model is used, one of the models in the SDLC (System Development Life Cycle). This waterfall model includes several stages in software development, such as: Analysis, Design, Coding, Testing, and Maintenance. This system is built using the PHP programming language with PHPMyadmin as administrator and MySQL for the database. The results of this study can be used and applied to support teaching and learning activities and can facilitate teachers and students, besides that students can access subject matter doing assignments or exercises via the web anytime anywhere according to their needs.